Genocidal processes: social death in Xinjiang. Issue 16 (10th December 2022) - Tobin, David
ABSTRACT: Genocide is a series of long-term processes emerging from "states of emergency" to convert targeted groups and secure the nation. This paper builds on Critical Genocide Studies literature to historically contextualize China's "fusion" policy, a narrative of emergency officially explaining extra-legal internment camps and inter-generational separation in Xinjiang. Although China's policymakers traditionally frame "one-nation-one-state thinking" as Western colonialism, critical approaches to Chinese politics show the party-state frames ethnic identities through colonial binaries of backward/modern and savagery/civilization. How does the party-state's "historic mission" to overcome colonial "humiliation" promote colonialism? The paper analyses how routine, dehumanizing official narratives of identity and danger enable genocides, conceptualized as planned processes of social death by attrition. It argues that contemporary "fusion" policy interweaves cultural superiority and ethnocentric developmentalism, seeking to resolve China's "ethnic problem" and decolonize Xinjiang through social death of Turkic Muslims.